2020
DOI: 10.1080/19476337.2020.1731610
|View full text |Cite
|
Sign up to set email alerts
|

High hydrostatic pressure stabilized micronutrients and shifted dietary fibers, from insoluble to soluble, producing a low-glycemic index mango pulp

Abstract: Nutritional authorities state that both total carbohydrates and low glycemic index (GI) diets affect glycemic control. High hydrostatic pressure (HHP) processing reduced the GI response of mango pulp when consumed by healthy adults. Present work evaluated the effects of HHP processing on concentrations of mango pulp dietary fiber sub-fractions (AOAC 2011.25 method), pectin methyl esterase (PME) activity, and established links with reduction of GI responses in healthy adults. Processing stability of mango pulp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…In this present study, HPP treatment of the banana and dragon fruit purees delayed the duration and concentration of blood glucose peak in mice compared with that obtained with the untreated control samples, whereas HPP‐treated cantaloupe puree did not cause changes in the postprandial blood glucose level. According to Elizondo‐Montemayor et al ., 7 HPP‐treated mango pulp had higher PME activity than its unprocessed counterpart, resulting in an increased interconversion of dietary fibre and the conversion of IDF to SDF. Furthermore, the concentration of non‐digestible oligosaccharides ( d ‐galacturonic acid) increased, resulting in the HPP‐treated mango pulp having a lower GI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this present study, HPP treatment of the banana and dragon fruit purees delayed the duration and concentration of blood glucose peak in mice compared with that obtained with the untreated control samples, whereas HPP‐treated cantaloupe puree did not cause changes in the postprandial blood glucose level. According to Elizondo‐Montemayor et al ., 7 HPP‐treated mango pulp had higher PME activity than its unprocessed counterpart, resulting in an increased interconversion of dietary fibre and the conversion of IDF to SDF. Furthermore, the concentration of non‐digestible oligosaccharides ( d ‐galacturonic acid) increased, resulting in the HPP‐treated mango pulp having a lower GI.…”
Section: Discussionmentioning
confidence: 99%
“…Fruits contain many active substances which are beneficial to human health. However, processed fruits rich in carbohydrates are often highly associated with metabolic diseases, especially in patients with glucose metabolic dysfunction caused by insufficient insulin secretion or the inability of cells to use insulin properly and whose blood glucose levels often remain high after consuming sugary fruits 7 . As fruits ripen, their carbohydrates are gradually hydrolysed by enzymes to free the monosaccharides, which increases both their sweetness and GI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in SDF was mainly due to the conversion of resistant maltodextrins, fructooligosaccharides, and galactooligosaccharides. 94 HHP treatment can also better maintain the original characteristics of prebiotics. Studies by Gomes et al have shown that, after HHP is used to treat cranberry juice with prebiotics, the juice still retains the properties of the prebiotics.…”
Section: ■ Process Of Screening Potential Prebioticsmentioning
confidence: 99%
“…It has been shown that HPP could improve carotenoids content in comparison to thermal treatments, for two fruit preparations [ 147 , 148 ]. In general, HPP has been shown to have minor or no significant effect on micronutrients [ 149 ] and on total the carotenoid content within vegetable matrices [ 150 ]. In general, HPP treatments below 50 °C caused no degradation of ascorbic acid in fruit preparation products [ 134 , 135 , 141 , 142 , 151 , 152 ].…”
Section: Impact Of Hpp On Antioxidant Activity During Storage Of Fruits and Fruit Productsmentioning
confidence: 99%